(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, one of the problems that arise in foreign language classes today is the problems related to the competence of reading comprehension and giving advice, recommendations, motivations based on scientific solutions to students, students and representatives of the younger generation, and a number of German international scientific facts are covered in the news presented by scientific experts.